Effect of Pb(ii) on phenanthrene degradation by new isolated Bacillus sp. P1. Issue 69 (29th July 2015) - Liu, Shao-Heng; Zeng, Guang-Ming; Niu, Qiu-Ya; Gong, Ji-Lai; Hu, Xin-Jiang; Lu, Lun-Hui; Zhou, Yao-Yu; Hu, Xi; Chen, Ming; Yan, Ming
<x xml:space="preserve">Abstract</x> A new strain of bacteria, Bacillus sp. P1, was isolated from compost to degrade PHE in the presence of Pb(ii).